Love from the crayons - Daywalt, Drew; Jeffers, Oliver; Daywalt, Drew. (New York : Penguin Workshop, 2019)
Discover all the bright colors and shades of love with the crayons.
Based on 'The day the crayons quit,' published in 2013.
1.8
K-3
Keywords: Colors -- Juvenile fiction; Crayons -- Juvenile fiction; Platonic love -- Juvenile fiction; Color -- Fiction; Crayons -- Fiction; Platonic love -- Fiction